Influence of Catecholamines (Epinephrine/Norepinephrine) on Biofilm Formation and Adhesion in Pathogenic and Probiotic Strains of Enterococcus faecalis - Cambronel, Mélyssa; Nilly, Flore; Mesguida, Ouiza; Boukerb, Amine Mohamed; Racine, Pierre-Jean; Baccouri, Olfa; Borrel, Valérie; Martel, Jérome; Fécamp, Florian; Knowlton, Rikki; Zimmermann, Kurt; Domann, Eugen; et al. (Frontiers in Microbiology, 2020)
Enterococcus faecalis has controversial status due to its emerging role in nosocomial infections, while some strains with beneficial effects are used as probiotics and starter cultures in dairy industry. These bacteria can be found as resident or transient germs in the gut or on skin, where they are continually exposed to various eukaryotic molecules. In this context, the aim of our work was to evaluate the effect of the catecholamine stress hormones, epinephrine (Epi) and norepinephrine (NE) on some Enterococcus strains. Four E. faecalis strains were included in this study: E. faecalis MMH594 and E. faecalis V583, pathogenic strains of clinical origin, E. faecalis Symbioflor 1 clone DSM 16431, a pharmaceutical probiotic, and E. faecalis OB15, a probiotic strain previously isolated from Tunisian rigouta (Baccouri et al, 2019). Epi was found to modulate the formation of biofilm (biovolume, thickness) in E. faecalis, whether pathogens or probiotics. NE had less effect on biofilm formation of these bacteria. We also investigated the effect of Epi and NE on adhesion of E. faecalis to eukaryotic cells as it is the first step of colonization of the host. Epi was found to significantly enhance the adhesion of MMH594 and OB15 to Caco-2/TC7 intestinal cells and HaCaT keratinocyte cells, whereas NE significantly increased the adhesion of V583 and Symbioflor 1 DSM 16431 to Caco-2/TC7 cell, the adhesion of MMH594, Symbioflor 1 DSM 16431, and OB15 to HaCaT cells. Analysis of a putative adrenergic sensor of Epi/NE in E. faecalis, compared to QseC, the E. coli adrenergic receptor, allowed the identification of VicK as the nearest protein to QseC with 29% identity and 46% similarity values. Structure modelling and molecular docking of VicK corroborated the hypothesis of possible interactions of this putative adrenergic sensor with Epi and NE, with binding energies of -4.08 and -4.49 kcal/mol, respectively. In conclusion, this study showed for the first time that stress hormones could increase biofilm formation and adhesion to eukaryotic cells in E. faecalis. Future experiments will aim to confirm by in vivo studies the role of VicK as adrenergic sensor in E. faecalis probiotic and pathogen strains.